2012
DOI: 10.1371/journal.pone.0051406
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Stroke Recurrence in Chinese Ischemic Stroke Patients – The ACROSS-China Study

Abstract: ObjectiveMetabolic syndrome has emerged as a novel risk factor in cardiovascular disease due to its potential for predicting stroke in population-based studies. We investigated the relationship of metabolic syndrome with stroke recurrence.MethodsThis was a retrospective analysis of Chinese patients enrolled in the prospective Abnormal gluCose Regulation in patients with acute strOke acroSS China (ACROSS-China) study after their first ischemic stroke. Metabolic syndrome was defined using the International Diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
1
15
1
1
Order By: Relevance
“…In this study, MetSyn prevalence in the ischaemic stroke subjects defined by IDF and HMS criteria are higher than in previous studies conducted among Chinese acute stroke subjects (51.35%), ischaemic stroke subjects in India (60%) and Iran (62%) [6] [10] [27]. The discrepancies could be due to the differences in proportions of co-morbidities among study subjects.…”
Section: Discussioncontrasting
confidence: 73%
“…In this study, MetSyn prevalence in the ischaemic stroke subjects defined by IDF and HMS criteria are higher than in previous studies conducted among Chinese acute stroke subjects (51.35%), ischaemic stroke subjects in India (60%) and Iran (62%) [6] [10] [27]. The discrepancies could be due to the differences in proportions of co-morbidities among study subjects.…”
Section: Discussioncontrasting
confidence: 73%
“…The risk of first stroke doubles with the presence of the metabolic syndrome, but recurrent stroke is not affected. [77][78][79][80][81][82] Diabetes mellitus worsens the outcomes from stroke, as it does in coronary artery disease. A study of nearly 12 000 community-dwelling men in western Australia found that diabetes mellitus significantly increased the risk of death in patients with stroke.…”
Section: Strokementioning
confidence: 99%
“…There are limited data, however, on the relationship between METS and the risk of stroke recurrence. Previous studies found that METS may not be predictive for stroke recurrence in patients with general ischemic stroke,8, 9 whereas another study demonstrated that METS was associated with higher risk of stroke recurrence in patients with ischemic stroke 10. The relationship between METS and recurrence of stroke after a stroke or TIA remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with a high risk of recurrence in patients with TIA or minor stroke were different from those of general stroke16; however, data from previous studies were derived from trials or cohorts in which patients were recruited weeks or months after their initial event and underestimated early recurrence, especially for minor stroke or TIA 8, 9, 17. Consequently, the risks of recurrent stroke caused by METS and DM in patients with a minor stroke or TIA should be further examined.…”
Section: Introductionmentioning
confidence: 99%